Out of Combat and Into the ClassroomHow Combat Experiences affect Combat Veteran Students in Adult Learning Environments - Maria L. Clark (Adult Education Research Conference, 2015)
This study sought to determine how combat experience affects GWOT veterans while participating in adult education. By exploring the effects of combat veterans’ experiences and the challenges they face, this study sought to learn what educators need to know about their difficulties and how it affects their learning.
Keywords: adult education; college; military; combat; veterans